Peningkatan Kompetensi Guru Paud dalam Menciptakan Mindful, Meaningful, dan Joyful Learning - Muniroh Munawar; Nia Lailin Nisfah (Mafapress Institut Pesantren Mathali'ul Falah Pati, 2026)
Early Childhood Education (ECE) teachers play a strategic role in creating learning environments that support children's optimal development. However, learning practices that focus primarily on academic achievement often limit opportunities for children to experience meaningful and enjoyable learning. This Community Service Program aimed to enhance ECE teachers’ competencies in designing and implementing mindful, meaningful, and joyful learning. The program involved ECE teachers from various institutions in Pati Regency and was conducted through training sessions, mentoring, group discussions, and practical lesson-planning activities. The implementation stages included needs assessment, material delivery, learning design workshops, and program evaluation. The results indicated an improvement in teachers’ understanding of child-centered learning, the application of mindfulness in educational interactions, strategies for creating meaningful learning experiences, and techniques for fostering joyful learning environments. Furthermore, participants demonstrated the ability to develop more creative, contextual, and developmentally appropriate learning plans. The program contributed positively to the enhancement of teachers’ professional competencies and supported the implementation of higher-quality learning practices in ECE settings. Therefore, continuous training and mentoring are recommended to strengthen the sustainable application of mindful, meaningful, and joyful learning in early childhood education institutions.